Setting the Stage for Teacher Engagement in a Professional Learning Community - Carmical, Mandee; Nadelson, Louis S (Advances in Social Sciences Research Journal, 2025)
Using a phenomenological methodology, we investigated how teachers’ professional needs, practices, and motivations align with the goals of a professional learning community designed to enhance teacher efficacy, promote reflective practice, and foster collaboration. We gathered data using semi-structured interviews. The teaching experience of our eight participating secondary teachers ranged from the first year to thirty-nine years in service. The teachers were in the beginning stage of a long-term grant-supported professional learning community initiative. We found a diversity of perspectives and practices ranging from traditional approaches to evolving perceptions of the teacher’s role in supporting learning. Our results also suggest that the brief engagement in the professional learning community initiative influenced the teachers' perceptions of teaching and learning. However, we were unable to find evidence of the teachers embracing educational innovations that led to transformations in their perceptions and practices. We conclude our report with a discussion of the findings, implications for the results, and recommendations for future research.